Self-Similar Polygonal Tiling. Issue 10 (1st December 2017) - Barnsley, Michael; Vince, Andrew
Abstract: The purpose of this paper is to give the flavor of the subject of self-similar tilings in a relatively elementary setting and to provide a novel method for the construction of such polygonal tilings.